Interactions between MCF-7 and MDA-MB-231 breast cancer cell lines and neutrophils : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Anatomy and Physiology at Massey University, Albany, New Zealand - Holland, Sherina (Massey University, 2019)
The tumour micro-environment (TME) has an essential role in tumour development and progression. Immune cells recruited to the site of the tumour secrete soluble factors such as proteinases, growth factors, survival factors and angiogenic factors into the TME. The secretion of these factors is up-regulated via inflammatory mediators secreted by tumour cells, resulting in a pro-malignant cycle between the cancer and immune cells. A greater understanding of the molecular mechanisms underpinning these interactions is required, as this will assist towards identifying potential new drug targets for cancer and ultimately, will aid in the long-term development of targeted and effective treatments for breast cancer and MBC. The activities of certain immune cells, such as tumour associated macrophages, have been reasonably well characterised in cancer, however, until recently, less was known regarding the role of neutrophils in tumour progression. The goal of the research described in this thesis was to determine whether soluble factors secreted by breast cancer cells might alter the phenotype or lifespan of neutrophils. The latter may allow neutrophils sufficient time to participate in activities within the TME that may either help or hinder tumour progression, while soluble factors released by the neutrophils might influence the invasiveness of breast cancer cells. To investigate whether soluble factors released by breast cancer cells could delay neutrophil apoptosis, neutrophils were cultured in conditioned medium (CM) prepared from highly metastatic MDA-MB-231 or poorly metastatic MCF-7 cells. Flow cytometry experiments showed a delay in apoptosis for neutrophils cultured in MDA-MB-231 CM, but not MCF-7 CM. Quantitative RT-PCR was used to measure neutrophil mRNA expression of pro- versus anti-apoptosis peptides; neutrophils incubated in MDA-MB-231 CM, but not MCF-7 CM, demonstrated a significantly higher expression of the anti-apoptosis peptide BCL2 (A1) and significantly lower expression of the pro-apoptosis peptide BAK compared to control. Western blots showed extensive caspase-8 activation for neutrophils cultured in MCF-7 CM, consistent with apoptosis, whilst neutrophils cultured in MDA-MB-231 CM showed little activation of caspase-8, indicating low levels of apoptosis. The soluble factor contained within the MDA-MB-231 CM, responsible for the delay in neutrophil apoptosis was found to be heat stable and have a molecular weight of between 10-100kDA. Prostaglandin E2 (PGE2) was identified as a potential candidate molecule, as it is a heat stable lipid, and when bound to plasma proteins, fits the molecular weight criteria. In addition, neutrophils cultured with 10μM native or heat treated PGE2 demonstrated a delay in apoptosis, however, this was to a lesser extent compared to neutrophils cultured in MDA-MB-231 CM. Cycoloxygenase-2 (COX-2), the enzyme responsible for PGE2 synthesis, was shown to be expressed in MDA-MB-231 cells but not MCF-7 cells, which is in agreement with the results demonstrating a delay in apoptosis for neutrophils cultured in MDA-MB-231 CM but not MCF-7 CM. Freshly isolated human neutrophils, obtained from the peripheral blood of healthy volunteers, cultured in MDA-MB-231 or MCF-7 CM for 7hrs were not polarised toward a pro or anti-tumour phenotype, as determined via the expression of ICAM-1 and MMP-9. Finally, to investigate whether neutrophils could influence the process of EMT and alter the migration of breast cancer cells, neutrophils were indirectly cultured, via transwell plates, with MDA-MB-231 or MCF-7 cells. Neutrophils were not found to enhance the migration of the cancer cells, as determined via a wound scratch assay. Likewise, neutrophils were not shown to influence the process of EMT in the cancer cells, as determined by changes to cell morphology or the expression of EMT markers.
Figures are re-used with permission.
Keywords: Breast; Cancer; Molecular aspects; Cancer cells; Secretions; Neutrophils; Apoptosis; 321101 Cancer cell biology